Concurrent chemoradiotherapy for bladder cancer: Practice patterns and outcomes in the general population. Issue 1 (April 2018) - Ghate, Ketan; Brennan, Kelly; Karim, Safiya; Siemens, D. Robert; Mackillop, William J.; Booth, Christopher M.
Abstract: Background: Clinical trials have shown that chemoradiotherapy (CRT) improves survival compared to radiation therapy (RT) alone in muscle-invasive bladder cancer. We describe uptake of CRT and comparative effectiveness in routine practice. Methods: Electronic treatment records were linked to the population-based Ontario Cancer Registry to identify all patients with bladder cancer treated with curative-intent RT in 1999–2013. Modified Poisson regression was used to analyze factors associated with use of CRT. Cox model and propensity score analyses were used to explore factors associated with cancer-specific (CSS) and overall survival (OS). Results: 1192 patients underwent RT during 1999–2013; median age was 79. Use of CRT increased over time: 36% (124/341) in 1999–2003, 38% (153/399) in 2004–2008, 48% (217/452) in 2009–2013 ( p = 0.001). Drug details were available for 82% (402/493) of CRT cases; the most common regimens were single-agent Cisplatin (57%, 230/402), single-agent Carboplatin (31%, 125/402) and 5-FU/Mitomycin (4%, 17/402). Factors associated with CRT include younger age ( p < 0.001), lower comorbidity ( p = 0.001), and geographic region (range 14–89%, p < 0.001). Five year CSS and OS among CRT cases were 45% (95%CI 39–51%) and 35% (95%CI 30–40%). On adjusted analyses CRT was associated with superior survival compared to RT (CSS HR 0.70, 95%CI 0.59–0.84; OS HR 0.74, 95%CI 0.64–0.85); results were consistent on propensity score analysis. There was significant improvement in survival of all RT-treated cases (irrespective or chemotherapy delivery) in 2009–2013 compared to 1999–2003 (CSS HR 0.77, 95%CI 0.61–0.97; OS HR 0.82, 95%CI 0.69–0.98). Conclusion: CRT is associated with superior survival compared to RT alone and its uptake corresponded to improved survival among all RT-treated cases in the general population. Uptake of CRT varies widely by geographic region.